Review on the pesticidal potential of Piperaceae against insect pests - Masdah Mawi; Anis Syahirah Mokhtar; Norhayu Asib (Penerbit Universiti Kebangsaan Malaysia, 2025)
Adverse effect of chemical pesticides on non- target organisms and environments leads the shifting to biopesticide implementation in agricultural industries in the recent years. Natural source biopesticide especially the plant-based biopesticide is gaining attention for their efficacy in controlling insects and because their application that employs Integrated Pest Management (IPM) approaches. Species from Piperaceae family are common herb which widely grown and spread throughout the world especially in Asia countries. Most of plants in the family contains various active chemical constituents that are responsible for biological and pharmacological activities. This paper aims to review and discuss the previous studies and research on the phytochemistry and insecticidal properties of Piper species in order to provide a scientific consensus for further research as a potential biopesticides. Further studies of Piperaceae plant are recommended to focus on their insecticidal actions on insect pests, thus, improving its benefits to non-target organisms and environment.